Analysis of OJK Policy in Supervising and Protecting Consumers in The Development of Financial Technology on Online Platforms (P2p) in Indonesia - Hasanah, Afifa Nur; Fradisa Bunga Riskia; Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The Financial Services Authority (OJK) has a crucial role in protecting consumers along with the development of Financial Technology (Fintech) Peer-to-Peer (P2P) Lending. . This research aims to determine the role and efforts of the Financial Services Authority (OJK) in protecting consumers. This research is qualitative research using the literature study method. This research identifies risks and vulnerabilities in the Fintech industry, as well as OJK's strategy in dealing with their negative impacts. The results demonstrate the need for strict regulation and a technology-based approach in the supervision of the financial industry. OJK also emphasizes the importance of financial literacy as a preventive measure. Thus, OJK strives to ensure that the development of Fintech P2P Lending provides optimal benefits so that it can protect consumer interests.